The influence of language proficiency, acculturation stress, and institutional support in enhancing personal development of international students in China - Muhammad Azram; Mei Hong; Waqar Ahmad; Ali Sohail; Bilal Ahmad (PLoS ONE, 2025)
This study highlights the significance of understanding how diversity experiences and innovative learning environments contribute to the personal development of international students in Higher Education Institutions (HEIs) in Shaanxi, China. Despite existing studies, there remains a notable gap in exploring their combined effects specifically within Chinese HEIs. This research aims to address this gap by analyzing the relationships among diversity experiences, language proficiency, and personal development, thereby offering valuable insights for educators and policymakers to enhance institutional support for international students. To achieve this, we conducted a quantitative survey involving 364 international students, utilizing a structured questionnaire and employing Structural Equation Modeling (SEM) for data analysis. The results reveal a positive relationship between diversity experiences and personal development. However, no direct relationship was found between innovative learning environments and personal development. Furthermore, language proficiency mediates the relationship between diversity experiences and personal development. Moreover, innovative learning environments were positively associated with both acculturation stress and language proficiency, which in turn were related to personal development. The findings underscore the vital role of institutional support in enhancing international students’ personal development through improved diversity experiences and language proficiency. To achieve this, educators and policymakers should integrate diversity initiatives and create adaptable learning environments that specifically address the needs of international students.